Penggunaan Artemisia absinthium L. dan Artemisia abrotanum L. di Bidang Kosmetologi - BEBY KELIDIA JEZMI (Yayasan Pendidikan Medika Indonesia, 2021)
Over the past few years, there has been an increasing interest in research on the chemical and biological activities of Artemisia species, including Artemisia absinthium L. and Artemisia abrotanum L. A. absinthium is an annual herbaceous plant that grows to a height of 80 cm and A. abrotanum where the flowering tips of shoots, dry, and has a gray-green color, slightly bitter taste and spicy citrus aroma. This species is found to have various functions, one of which is in the field of cosmetology. To find out more about the use of Artemisia absinthium L. and Artemisia abrotanum L. in the field of cosmetology using the method, namely the study of literature from international journals by summarizing the topic of discussion and comparing the results presented in the article. The use of Artemisia absinthium L. and Artemisia abrotanum L. various parts of the plant in cosmetic production, namely the extract part is then used as a source of cosmetic raw materials, especially in Southeast Asia, North America and Europe.